High resistance towards herbivore-induced habitat change in a high Arctic arthropod community - Niels M. Schmidt; Jesper B. Mosbacher; Bernhard Eitzinger; Eero J. Vesterinen; Tomas Roslin (ROYAL SOC, 2022)
Mammal herbivores may exert strong impacts on plant communities, and are often key drivers of vegetation composition and diversity. We tested whether such mammal-induced changes to a high Arctic plant community are reflected in the structure of other trophic levels. Specifically, we tested whether substantial vegetation changes following the experimental exclusion of muskoxen (Ovibos moschatus) altered the composition of the arthropod community and the predator-prey interactions therein. Overall, we found no impact of muskox exclusion on the arthropod community: the diversity and abundance of both arthropod predators (spiders) and of their prey were unaffected by muskox presence, and so was the qualitative and quantitative structure of predator-prey interactions. Hence, high Arctic arthropod communities seem highly resistant towards even large biotic changes in their habitat, which we attribute to the high connectance in the food web.